Cell cycle regulation as a mechanism for functional separation of the apparently redundant uracil DNA glycosylases TDG and UNG2 - Hardeland, Ulrike (Oxford University Press, 2007)
Human Thymine-DNA Glycosylase (TDG) is a member of the uracil DNA glycosylase (UDG) superfamily. It excises uracil, thymine and a number of chemical base lesions when mispaired with guanine in double-stranded DNA. These activities are not unique to TDG; at least three additional proteins with similar enzymatic properties are present in mammalian cells. The successful co-evolution of these enzymes implies the existence of non-redundant biological functions that must be coordinated. Here, we report cell cycle regulation as a mechanism for the functional separation of apparently redundant DNA glycosylases. We show that cells entering S-phase eliminate TDG through the ubiquitin–proteasome system and then maintain a TDG-free condition until G2. Incomplete degradation of ectopically expressed TDG impedes S-phase progression and cell proliferation. The mode of cell cycle regulation of TDG is strictly inverse to that of UNG2, which peaks in and throughout S-phase and then declines to undetectable levels until it appears again just before the next S-phase. Thus, TDG- and UNG2-dependent base excision repair alternates throughout the cell cycle, and the ubiquitin–proteasome pathway constitutes the underlying regulatory system.